2004
DOI: 10.1007/s00134-004-2236-2
|View full text |Cite
|
Sign up to set email alerts
|

Transaminase levels in ventilated children with respiratory syncytial virus bronchiolitis

Abstract: RSV disease in ventilated children was more severe if transaminase levels were elevated. Transaminase level elevation was due to hepatitis in the majority of patients. In patients with congenital heart disease we also detected myocardial involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 10 publications
0
33
1
1
Order By: Relevance
“…Elevated transaminase levels have been found in 46 to 49% of ventilated children with RSV bronchiolitis [35,36]. Severe hepatitis with alanine aminotransferase levels of nearly 3,000 IU/l has been noted and this was associated with coagulopathy [35].…”
Section: Resultsmentioning
confidence: 99%
“…Elevated transaminase levels have been found in 46 to 49% of ventilated children with RSV bronchiolitis [35,36]. Severe hepatitis with alanine aminotransferase levels of nearly 3,000 IU/l has been noted and this was associated with coagulopathy [35].…”
Section: Resultsmentioning
confidence: 99%
“….02 a Duration of MV, days, median (IQR) 5 (4-6) 4 (2.8-4.3) 5 (4.5-5) 6 (5.5-9) Ͻ.01 a Duration of PICU stay, days, median (IQR) 6 (4-8.8) 5 (3.5-6.8) 6 (4.5-8) 9 (7)(8)(9)(10)(11)(12) . tween measurements.…”
Section: Discussionmentioning
confidence: 99%
“…We used length of ventilation and PICU stay as our outcome measures. ALT was used as a marker of bronchiolitis severity (7). We do not use the Pediatric Logistic Organ Dysfunction score as an outcome measure because of the large gaps in predicted risk of mortality and our concerns about its clinical applicability (8).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies found that patients with acutely elevated intrapulmonary pressure resulting from bronchospasm [2] and severe respiratory syncytial viral lung disease leading to hyperinflation [3] exhibited evidence of myocardial injury, such as elevated cardiac troponin levels; this was probably due to strain imposed on the right ventricle by pulmonary hypertension. Ventricular strain has previously also been associated with elevated hyaluronate levels [4].…”
mentioning
confidence: 99%